Maternal Blood Group and Routine Direct Antiglobulin Testing in Neonates: Is There a Role for Selective Neonatal Testing? - Hwazen A. Shash; Suzan A. Alkhater (Children, 2021)
Recommendations for the screening of hemolytic disease of the newborn (HDN) advise taking a selective approach in using the direct antiglobulin test (DAT) for mothers with blood group O or RhD-negative. This study assessed the relation of DAT results to maternal and neonatal blood groups and evaluated the risk of HDN. A retrospective analysis of all healthy newborns admitted during 2018 was performed. Of 1463 newborns, 4.4% had a positive DAT. There were 541 (37%) maternal–neonatal pairs with ABO incompatibility, most commonly born to mothers with blood group O. The cohort of neonates born to mothers with blood group O was divided into three groups: the O-A and O-B groups and the O-O group as a control. The DAT was positive in 59 (8.3%) neonates; most were in the O-B group (49.2%), whereas 13.6% were in the control group (p < 0.01). While the neonates in the O-B group were more likely to require phototherapy (p = 0.03), this finding was not related to DAT results. We found that selective testing of mothers with blood group O, mothers with blood group O or RhD-negative, neonates with blood group B, and neonates with blood group B born to mothers with blood group O or RhD-negative was ineffective in detecting phototherapy requirements. Our results indicate no difference regarding the need for phototherapy in neonates born to mothers with different blood types regardless of the DAT results.